Hypoxia-inducible factor 2α: a novel target in gliomas. (9th August 2018) - Renfrow, Jaclyn J; Soike, Michael H; Debinski, Waldemar; Ramkissoon, Shakti H; Mott, Ryan T; Frenkel, Mark B; Sarkaria, Jann N; Lesser, Glenn J; Strowd, Roy E
Hypoxia is an important contributor to aggressive behavior and resistance mechanisms in glioblastoma. Upregulation of hypoxia inducible transcription factors (HIFs) is the primary adaptive cellular response to a hypoxic environment. While HIF1α has been widely studied in cancer, HIF2α offers a potentially more specific and appealing target in glioblastoma given expression in glioma stem cells and not normal neural progenitors, activation in states of chronic hypoxia and expression that correlates with glioma patient survival. A first-in-class HIF2α inhibitor, PT2385, is in clinical trials for renal cell carcinoma, and provides the first opportunity to therapeutically target this important pathway in glioma biology.